Grammatical similarity and its role in work - محمد, معاذ (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
This research handles the phenomenon of similarity and its effect in syntax, for three are letters or names that do not function in dependently; rather they are in need for being similar to a verb so that they can function; this research , then, studies the reasons that enabled these letters and nouns, which look verb, to function, addressing thus the similarity verbally and semantically, it also includes verbs whose meanings are the same as other verbs, so that they function differently, there is also the one that is more like the verb; that is the similarity of the second ration such as the verbal adjective and "LA" which functions just like these letters, finally, the research tackles the study of perfect similarity in signification between relative noun and conditional noun; because this shared in signification led one into functioning like the other.